Keanekaragaman Semut (Hymenoptera: Formicidae) pada Berbagai Subzona Hutan Pegunungan di Sepanjang Jalur Pendakian Cibodas, Taman Nasional Gunung Gede-Pangrango (TNGGP) - Arifin, Irfanul (Bioma, 2014)
Abstract The existence of ants in the nature are influenced by biotic and abiotic components. Different of conditions in a habitat determine biodiversity inside, belonging to ants diversity. This research was aim to know diversity, richness, and distribution of ants in various Mountain Forest Subzone in along Cibodas Climbing Track, TNGGP. It was first study about ants of TNGGP because no previous research was held so that can becomed reference for next research and conservation step. The used method was descriptive with survey technique of pit fall trap by alcohol located in 3 mountain forest subzones for 6 position that were Telaga Biru, Cibeureum waterfall, Air Panas, Kandang Badak, Mount Gede Summit, and Alun-Alun Suryakencana. This research has identified 4 subfamilies and 12 species. Diversity index of submontane, montane, and subalpine forest severally was about 1.568, 1.347, and 0.676. Key words: ants diversity, Cibodas climbing track, montane, pit fall trap, subalpine, submontane